Titanium microalloyed steels. (2nd January 2019) - Baker, T. N.
ABSTRACT: Compared with niobium and vanadium, titanium has been regarded as a relative minor element in microalloyed (MA) steels. More recently, titanium compounds in MA steels have been recognised as having a wider role than just involved in austenite grain refinement. A brief history is followed by considering the physical state of titanium and its compounds characterized in MA steels. Their solubility in iron and the morphology of the precipitates they form, lead to their functions in controlling mechanical and toughness properties of MA steels often involving the multiple alloying with niobium, vanadium, carbon and nitrogen. Titanium has become an important element in the development of linepipe steels, which can develop bainite/acicular ferrite (AF) microstructures. The influence of Ti on nucleation of AF is an active research area, particularly in welding of MA steels. Finally, the influence of titanium on hot ductility, continuous casting and thin slab direct-charging processes is discussed.